Body mass index and psychological distress among Lebanese University students: examining the moderating effect of gender. Issue 3 (2nd July 2016) - Abou Abbas, Linda; Salameh, Pascale; Nasser, Wissam; Nasser, Zeina; Godin, Isabelle
Abstract: Studies investigating the association between body mass index (BMI) and psychological distress (PD) have shown contradictory results. The present study examined the relationship between BMI and PD among Lebanese university students and tested its moderation by gender. A cross-sectional study was conducted using a proportionate cluster sampling of university students. Data concerning socio-demographic characteristics, body weight and height, tobacco consumption, physical activity, presence of chronic diseases and self-rated global health were collected. PD was assessed using Beirut Distress Scale (BDS-22). Students were classified as underweight (BMI <18.5 kg/m 2 ), normal weight (BMI 18.5–24.9 kg/m 2 ), overweight (BMI 25–29.9 kg/m 2 ) and obese (BMI >30 kg/m 2 ). The association between BMI and BDS-22 differed by gender ( p -value for interaction: .02). Being overweight was inversely associated with BDS-22 for females only (adjusted OR .5, 95% CI: .4–.8, p -value .02). Neither obesity nor underweight was associated with PD for both genders.